Identitas Dakwah Perempuan dengan Techno-Religion - Pambayun, Ellys Lestari (Fakultas Dakwah dan Ilmu Komunikasi, Universitas PTIQ Jakarta, 2020)
The issue that is the focus of this paper is the phenomenon of identity formation that is built through da'wah conveyed by women on social media, such as the Gender Studies Community (Ustazah Nur Rodiah), the Niqab Squad (Indardari and Dina Nurlina), and Mumpuni Handayekti. The ustazahs who understand Islam seem to be a reference for the public because of their understanding and mastery of verses, hadiths, religious studies, and interpretations which are the content of their platforms at any time. On the one hand, the convenience of social media as a source of da'wah content has triggered the emergence of